2016
DOI: 10.5101/nbe.v8i4.p246-267
|View full text |Cite
|
Sign up to set email alerts
|

Metal, Metalloid, and Oxide Nanoparticles for Therapeutic and Diagnostic Oncology

Abstract: Nanoparticles have comprehensively affected various sights of human life. Through the wide range of claims about nanosized particles and their functions, biomedical applications are of much interest among health care researchers due to the nanoparticles' potential for use in the process of disease diagnosis, control and treatment. In this regard, inorganic nanoparticles, which have high potential in diagnostic and therapeutic systems, have recently received much attention in oncology. Although inorganic nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 176 publications
(180 reference statements)
1
15
0
Order By: Relevance
“…9 Moreover, it is well documented in the literature that nano-Se, regardless of the method of its synthesis, induces apoptosis by depletion of mitochondrial membrane potential, cytochrome c release and production of ROS. 53 Indeed, SeNps were found to induce the formation of ROS in HT29 cells in a concentration dependent manner evident by the DCFDA (Carboxy-H 2 DCFDA: 6-carboxy-2',7'-dichlorodihydrofluorescein diacetate) flow cytometry histograms in Fig. 5.…”
Section: Senps Modulate the Protein Levels Of Apoptosis-related Molecmentioning
confidence: 94%
See 1 more Smart Citation
“…9 Moreover, it is well documented in the literature that nano-Se, regardless of the method of its synthesis, induces apoptosis by depletion of mitochondrial membrane potential, cytochrome c release and production of ROS. 53 Indeed, SeNps were found to induce the formation of ROS in HT29 cells in a concentration dependent manner evident by the DCFDA (Carboxy-H 2 DCFDA: 6-carboxy-2',7'-dichlorodihydrofluorescein diacetate) flow cytometry histograms in Fig. 5.…”
Section: Senps Modulate the Protein Levels Of Apoptosis-related Molecmentioning
confidence: 94%
“…Noteworthy, HT29, the human colon cancer cell line studied in this work, has been previously reported to be sensitive to nano-Se. 53,54 Subsequently, focusing on HT29 colon cancer cells of human origin, we observed that part of the antiproliferative effects exerted by SeNps, LCSe or LC, can be attributed to the induction of apoptotic cell death. For the comparative analysis of the apoptotic effects induced by SeNps, LCSe and LC, the time-dependent dynamic process of apoptosis for each treatment group was studied in a pre-defined time frame (20 -26 h) for 10 8 CFUs/ml for LC and LCSe or 15 μg/ml for SeNps (15 μg of SeNps were extracted from 10 8 CFUs of LCSe) by flow cytometric analysis of the double AnnexinV-FITC/PI (AnnexinV-Fluorescein isothiocyanate / Propidium iodide) staining.…”
Section: Comparative Analysis Of the In Vitro Antiproliferative And Pmentioning
confidence: 99%
“…Superparamagnetic iron oxide nanoparticles (SPIONs), as the main subset of magnetic nanoparticles (NPs), have attracted the researchers' interest in many fields, especially modern medicine [1]. Their unique attributes, arising from their quantum size, large surface/volume ratio, thermal energy, and minimal side effects, making them a promising tool in biological applications [2,3]. These versatile nanoplatforms can be used in the diagnosis (cellular and functional magnetic resonance imaging, biosensors, and immunoassays), treatment (targeted drug or gene delivery, hyperthermia, and thrombolysis), and monitoring of diseases outcomes (tissue repair fluids and tissue engineering [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have identified many classes of natural as well as synthetic organoselenium compounds which act as cytotoxic agents, and the research is ongoing for identifying more such compounds (154)(155)(156)(157). Keeping in mind the immunomodulatory function of selenium, selenium nanoparticles (SeNPs) have been synthesized (158,159). SeNPs have potential to decrease tumor cell proliferation, drive the anti-tumor function of TAMs, and in virtue of their properties, be used for imaging diagnosis and cancer therapy with low costs and negligible side effects (154,158,159).…”
Section: Opportunities For Improvement Of Cancer Therapymentioning
confidence: 99%
“…Keeping in mind the immunomodulatory function of selenium, selenium nanoparticles (SeNPs) have been synthesized (158,159). SeNPs have potential to decrease tumor cell proliferation, drive the anti-tumor function of TAMs, and in virtue of their properties, be used for imaging diagnosis and cancer therapy with low costs and negligible side effects (154,158,159). An impressive number of in vitro and in vivo studies clearly confirms the scarce toxicity of selenium compounds as monotherapy and in combination with classical chemotherapy (154).…”
Section: Opportunities For Improvement Of Cancer Therapymentioning
confidence: 99%